Kebijakan UMKM Nuriza Snack dalam Meningkatkan Produktivitas, Efisiensi, dan Pendapatannya - Erika Gustian Fauzi; Dian Sabrina Syaharni; Salsabillah Sirait (POINT: Jurnal Ekonomi dan Manajemen, 2021)
The company will be very dependent on proper management management. Productivity, efficiency, and income are characteristics of companies that can advance and develop every period.Various policies are also carried out to overcome existing problems or to prevent the occurrence of these problems.The company also began to identify business processes in order to manage each part in detail.In the current pandemic era, companies will continue to strive to minimize the occurrence of problems that can hamper productivity performance, efficiency and revenue.The existence of evaluation will also be the basis for determining every policy set, from which the company is expected to be able to carry out all kinds of policies consistently, so as to minimize the existence of problems. Keywords: Management, Policy, Evaluation.